Comparison of properties inherent to thin titanium oxide films formed by rapid thermal annealing on SiC and porous SiC substrates - Bacherikov, Yu.Yu.; Dmitruk, N.L.; Konakova, R.V.; Kolomys, O.F.; Okhrimenko, O.B.; Strelchuk, V.V.; Lytvyn, O.S.; Kapitanchuk, L.M.; Svetlichnyi, A.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2018)
The comparative analysis of optical characteristics inherent to TiO₂/SiC and TiO₂/por-SiC/SiC structures has been performed. It has been shown that, in these structures, regardless of the substrate structure, formation of TiO₂ layers with approximately the same width, 60 nm, takes place. In this case, the TiO₂ film composition is close to the stoichiometric one. At the same time, the presence of an additional porous layer in the TiO₂/por-SiC/SiC structure leads to blurring the oxide film – substrate interface but promotes an increase in the intensity of the Raman scattering signal from the oxide film.